2012
DOI: 10.1097/aln.0b013e31825154d2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxygen Saturation Measured by Near-infrared Spectroscopy and Jugular Venous Bulb Oxygen Saturation during Arthroscopic Shoulder Surgery in Beach Chair Position under Sevoflurane-Nitrous Oxide or Propofol-Remifentanil Anesthesia

Abstract: Background:We examined the effects of different anesthetics on cerebral oxygenation and systemic hemodynamics in patients undergoing surgery in beach chair position (BCP). Jugular venous bulb oxygen saturation (SjvO 2 ) and regional cerebral tissue oxygen saturation (SctO 2 ) were determined while patients were placed from the supine to BCP. Whether SctO 2 and SjvO 2 are interchangeable in assessing the cerebral oxygenation was also examined. Methods: Forty patients undergoing shoulder surgery in BCP were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 58 publications
3
67
1
1
Order By: Relevance
“…Collectively, it might be concluded that general anesthesia using sevoflurane in combination with some vasoactive agents including phenylephrine may modulate hemodynamic changes according to the beach chair position. Indeed, a recent study has documented that sevoflurane-nitrous oxide, but not propofol-remifentanil, anesthesia affords an advantage to stabilize the mean blood pressure in the beach chair position [3]. Irrespective of decreases in both blood pressure and heart rate, the beach chair position under general anesthesia did not alter the cerebral TOI values throughout the current study.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Collectively, it might be concluded that general anesthesia using sevoflurane in combination with some vasoactive agents including phenylephrine may modulate hemodynamic changes according to the beach chair position. Indeed, a recent study has documented that sevoflurane-nitrous oxide, but not propofol-remifentanil, anesthesia affords an advantage to stabilize the mean blood pressure in the beach chair position [3]. Irrespective of decreases in both blood pressure and heart rate, the beach chair position under general anesthesia did not alter the cerebral TOI values throughout the current study.…”
Section: Discussionmentioning
confidence: 52%
“…First, sevoflurane, compared with isoflurane, reportedly well preserves dynamic cerebral pressure autoregulation in humans [16]. Sevofluranenitrous oxide, but not propofol-remifentanil, anesthesia keeps up cerebral oxygen saturation measured by near-infrared spectroscopy as well as jugular venous bulb oxygen saturation in the beach chair position [3]. These results suggest that sevoflurane favors maintenance of cerebral oxygenation in the beach chair position.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…At the present time, neither SctO 2 nor SvjO 2 has proven to be useful in this setting [9,17]. The threshold to identify cerebral ischemia with SctO 2 and SvjO 2 remains unknown and is influenced by the cerebral metabolic rate for O 2 to cerebral blood flow ratio, patient cerebrovascular disease, and technology-dependent variables.…”
Section: Discussionmentioning
confidence: 92%
“…3 The impact of extracranial contamination on cerebral oxygenation values indeed depends on the technology employed. However, changes in jugular venous bulb oxygenation 4 and middle cerebral artery blood velocity 5 were reported in patients in the upright position, suggesting a large intracranial contribution to the measured value.…”
Section: To the Editormentioning
confidence: 88%